Sugarcane Variety Census: Florida 2001 - B. Glaz; Robert A. Gilbert (EDIS)
This annual variety census of the Florida sugarcane industry for the 2001-2002 harvest season is the latest in a series of annual reports. Mill managers and independent growers supplied data for all of Florida's sugarcane acreage. As a result, the census contains much descriptive and useful information for the Florida sugarcane industry. This document is SS AGR 198, a publication of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2003. Reviewed March 2005.